Shifting Prophecy - Baruah, Merajur Rahman (Public Service Broadcasting Trust, 2007)
Verzio FF Submission Duration: 00:31:00 The film explores the emergence of a rural Muslim women’s rights movement in the state of Tamil Nadu, India. These women struggle against discrimination and try to give a voice to those who never had a chance to have a say in their lives. They struggle tirelessly against the ruling patriarchal social order and even build the world’s first ever women’s mosque.